A novel case of food poisoning caused by the consumption of Pacific bluefin tuna infected with Kudoahexapunctata. Issue 6 (17th June 2021) - Tachibana, Takayuki; Watari, Takashi
Abstract: Consumption of Japanese cuisine, such as sushi and sashimi, is accompanied by the risk of food poisoning through various pathogens. Kudoa hexapunctata, detected in both adult and juvenile Pacific bluefin tuna, causes foodborne diseases. Here, we report cases of food poisoning after Kudoa hexapunctata ‐infected PBT consumption. We suggest that medical history about the fish used in sashimi and sushi preparation is used to assist in making the diagnosis as Kudoa infection. Abstract : Kudoa hexapunctata spores.